Does bronchopulmonary dysplasia contribute to the occurrence of cerebral palsy among infants born before 28 weeks of gestation?. Issue 1 (24th August 2010) - Van Marter, Linda J; Kuban, Karl C K; Allred, Elizabeth; Bose, Carl; Dammann, Olaf; O'Shea, Michael; Laughon, Matthew; Ehrenkranz, Richard A; Schreiber, Michael D; Karna, Padmani; Leviton, Alan; ,
Abstract : Objective: To evaluate the relationships among cerebral palsy (CP) phenotypes and bronchopulmonary dysplasia (BPD) severity and, in the process, to generate hypotheses regarding causal pathways linking BPD to CP. Study design: We studied 1047 infants born before the 28th week of gestation. Receipt of supplemental oxygen at 36 weeks postmenstrual age (PMA), with or without the need for mechanical ventilation (MV) at 36 weeks PMA, defined two levels of BPD. At 24 months, the children underwent neurologic examinations and CP diagnoses were made using an algorithm based on topographic localisation. Results: The 536 infants with BPD were at increased risk of all three CP phenotypes. In time-oriented multivariable analyses that adjusted for potential confounders, receipt of supplemental oxygen without MV at 36 weeks PMA (BPD) was not associated with increased risk of any CP phenotype. In contrast, BPD accompanied by MV at 36 weeks PMA (BPD/MV) was associated with a nearly sixfold increased risk of quadriparesis and a fourfold increased risk of diparesis. Conclusions: Combined treatment with both MV and supplemental oxygen at 36 weeks PMA strongly predicts the more common bilateral CP phenotypes. BPD without MV at 36 weeks PMA was not significantly associated with any form of CP.